Mapping the body, embodying the map : a corporeal taxonomy into a topographical transformation at the border of Nicosia - Georgiou, Christina (My University, 2013)
Mapping the Body, Embodying the Map: A corporeal taxonomy into a topographical transformation at the border of Nicosia is a project realized along and across the buffer zone within the Venetian walls of Nicosia, the capital city of Cyprus. The focus of this project is the area that divides the city into two parts and it has been mentioned as buffer zone, green line, borderline, dividing line, dead zone and many more. This restricted area has activated not only physical barriers for people but also caused emotional and mental restrain. The motivation is my wish to reveal the significance of this area and uncover the impact it creates on the body: physical, mental and emotional. Also my intention is to deform and reconstruct the psychophysical perceptions of the dividing line through artistic means. The approach and method of working consists of artistic research, and a practical and theoretical framework. I have used live performance as my creative technique to realize a series of site-specific performance interventions along and across the Nicosia buffer zone in order to generate knowledge about that area, examined in my research. In addition, the written part of this project includes a description and analysis of my artistic work at the border, supported with theories focusing mainly on José Esteban Muñoz’s work, “Disidentifications” (1999) and Sarah Pink’s “Doing Sensory Ethnography” (2009). This thesis project questions: How the conventional idea of the border and its solidified historicity can be transformed to a new perception through performing, while bringing a psychophysical transformation to this experience? To come to an answer, the body is used as a tool to create live actions and the Nicosia border is used as a site to be experienced through non covnentional ways. Finally, the outcome is an experiential mapping, which is shaped while the body is used to measure, archive, experience and re-experience, and therefore memorize the border anew.
Keywords: Nicosia border; body; mapping; disidentification; live art; psychogeography; Site-specific art.; Performance art.; Action in art.; performanssi; rajavyöhykkeet; paikkasidonnainen taide; ruumiillisuus; esitystaide; Nikosia; performance; gränszoner; platsspecifik konst; kroppslighet; LAPS